A concept of convergence in geodesic spaces - W. A. Kirk (2018)
A CAT(0) space is a geodesic space for which each geodesic triangle is at least as 'thin' as its comparison triangle in the Euclidean plane. A notion of convergence introduced independently several years ago by Lim and Kuczumow is shown in CAT(0) spaces to be very similar to the usual weak convergence in Banach spaces. In particular many Banach space results involving weak convergence have precise analogues in this setting. At the same time, many questions remain open. © 2007 Elsevier Ltd. All rights reserved.